2019
DOI: 10.1097/aud.0000000000000591
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Discrimination of Speaking Style Under Cochlear Implant Simulation

Abstract: The findings from the present study demonstrate that perceiving differences in three speaking styles under CI simulation is a difficult task because some important cues to speaking style are not fully available in these conditions. While some cues like speaking rate are available, this information alone may not always be a reliable indicator of a particular speaking style. Some other reliable speaking styles cues, such as degraded acoustic-phonetic information and variability in speaking rate within an utteran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(22 citation statements)
references
References 65 publications
2
20
0
Order By: Relevance
“…For each talker, 12 utterances were produced each in the context of a conversation (conversational reduced-"conversational"), from the retelling of a story (retold story-"neutral"), and from a read list (read text-"clear"), for 36 in total. A full description of the acousticphonetic characteristics of a larger set of materials from which the stimuli were selected can be found in the study methods provided in Tamati et al (2019). As summarized in Tamati et al (2019), the clear speech (read text) originating from the larger corpus demonstrated properties consistent with a carefully articulated speaking style: a greater relative number of pauses, a slower speaking rate (although varying across talkers), a higher average F0 and F0 range, and more fully realized sound segments, including more frequent wordfinal [t]-realization, schwa realization in unstressed syllables, word-final [n]-realization, and postvocalic-[r]realization.…”
Section: B Materialsmentioning
confidence: 99%
See 3 more Smart Citations
“…For each talker, 12 utterances were produced each in the context of a conversation (conversational reduced-"conversational"), from the retelling of a story (retold story-"neutral"), and from a read list (read text-"clear"), for 36 in total. A full description of the acousticphonetic characteristics of a larger set of materials from which the stimuli were selected can be found in the study methods provided in Tamati et al (2019). As summarized in Tamati et al (2019), the clear speech (read text) originating from the larger corpus demonstrated properties consistent with a carefully articulated speaking style: a greater relative number of pauses, a slower speaking rate (although varying across talkers), a higher average F0 and F0 range, and more fully realized sound segments, including more frequent wordfinal [t]-realization, schwa realization in unstressed syllables, word-final [n]-realization, and postvocalic-[r]realization.…”
Section: B Materialsmentioning
confidence: 99%
“…A full description of the acousticphonetic characteristics of a larger set of materials from which the stimuli were selected can be found in the study methods provided in Tamati et al (2019). As summarized in Tamati et al (2019), the clear speech (read text) originating from the larger corpus demonstrated properties consistent with a carefully articulated speaking style: a greater relative number of pauses, a slower speaking rate (although varying across talkers), a higher average F0 and F0 range, and more fully realized sound segments, including more frequent wordfinal [t]-realization, schwa realization in unstressed syllables, word-final [n]-realization, and postvocalic-[r]realization. The characteristics of the clear speech are described in contrast with the conversational speech originating from the larger corpus (conversational reduced), which demonstrated features more consistent with conversational speech: faster speaking rate, a lower average F0 and F0 range, and more frequent reduction/deletion of the four sound segments.…”
Section: B Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…In principle, high-and low-performing CI users might represent two distinct groups of patients whose outcomes may be more specifically predicted by differences in underlying neurocognitive functioning and auditory skills. These two groups often show large differences in performance in speech recognition tasks: low-performing CI users are more susceptible to noise (e.g., Fu and Nogaki) 15 , as well as other sources of signal degradations, such as speech variability (e.g., Tamati et al) 51 . Furthermore, although both groups perform more poorly under adverse listening conditions, it appears that some high-performing CI users are better able to take advantage of top-down compensatory mechanisms (Bhargava et al) 4 .…”
Section: Introductionmentioning
confidence: 99%